179k views
2 votes
Please answer, thank you

Please answer, thank you-example-1
User Ted Graham
by
5.2k points

1 Answer

1 vote

Answer:

Explanation:

Since y = -3 we can plug straight into the other equation

--> -x + 2y = -6

-x + 2(-3) = -6

-x - 6 = -6

-x = 0

x = 0

To graph this draw a horizontal like across the page at y = -3 and a vertical line down the page to represent x = 0

The point where these lines intersect is (0,-3)

So that would be the ordered pair solution.

User Uut
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.